Health-economic evaluation of home telemonitoring for COPD in Germany: evidence from a large population-based cohort - Achelrod, Dmitrij (Eur J Health Econ, 2016)
INTRODUCTION: Telemonitoring for COPD has gained much attention thanks to its potential of reducing morbidity and mortality, healthcare utilisation and costs. However, its benefit with regard to clinical and economic outcomes remains to be clearly demonstrated. OBJECTIVE: To analyse the effect of Europe’s largest COPD telemonitoring pilot project on direct medical costs, health resource utilisation and mortality at 12 months. METHODS: We evaluated a population-based cohort using administrative data. Difference-in-difference estimators were calculated to account for time-invariant unobservable heterogeneity after removing dissimilarities in observable characteristics between the telemonitoring and control group with a reweighting algorithm. RESULTS: The analysis comprised 651 telemonitoring participants and 7047 individuals in the standard care group. The mortality hazards ratio was lower in the intervention arm (HR 0.51, 95 % CI 0.30–0.86). Telemonitoring cut total costs by 895 € (p < 0.05) compared to COPD standard care, mainly driven by savings in COPD-related hospitalisations in (very) severe COPD patients (−1056 €, p < 0.0001). Telemonitoring enrolees used healthcare (all-cause and COPD-related) less intensely with shorter hospital stays, fewer inpatient stays and smaller proportions of people with emergency department visits and hospitalisations (all p < 0.0001). Reductions in mortality, costs and healthcare utilisation were greater for (very) severe COPD cases. CONCLUSION: This is the first German study to demonstrate that telemonitoring for COPD is a viable strategy to reduce mortality, healthcare costs and utilisation at 12 months. Contrary to widespread fear, reducing the intensity of care does not seem to impact unfavourably on health outcomes. The evidence offers strong support for introducing telemonitoring as a component of case management.